Determination of Ca content of coral skeleton by analyte additive method using the LIBS technique - Haider, A F M Yusuf; Khan, Z.H. (© 2012 Elsevier Ltd., 2017)
This article was published in the Journal Optics and Laser Technology [© 2012 Elsevier Ltd. ] and the definite version is available at : 10.1016/j.optlastec.2012.01.032